KINERJA PEGAWAI KELURAHAN JATIMAKMUR DIPENGARUHI OLEH PEMBERIAN MOTIVASI MELALUI DISIPLIN KERJA - Eddy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
To determine the effect of positive and significant motivation on employee performance through work discipline at the Jatimakmur Village Office. This research was conducted on employees of the Jatimakmur Village Office. The data collection method used is by distributing questionnaires. In this study, the researcher used the saturated sample method. For the data analysis model, the researcher uses path analysis test (path analysis).Motivation has a positive and significant effect on employee performance at the Jatimakmur Village Office, work discipline has a positive and significant effect on employee performance at the Jatimakmur Village Office, motivation has a positive and significant effect on employee work discipline at the Jatimakmur Village Office, motivation has a positive and significant effect on employee performance through work discipline at the Jatimakmur Village Office.